Aspleniaceae (Polypodiopsida) do corredor de biodiversidade do norte do Pará, Brasil: um fragmento do Centro de Endemismo Guiana - GÓES NETO, Luiz Armando de Araújo (2015)
This paper is part of a series that will treat the lycophyte and fern species of the Northern Pará Biodiversity Corridor, and is part of the project "Diagnóstico da Biodiversidade das Unidades de Conservação Estaduais do Mosaico Calha Norte, Estado do Pará". Aspleniaceae are treated in this article, and an identification key, illustrations, geographic distributions, brief descriptions, and taxonomic comments are provided. There are eight species of Aspleniaceae in this region (Asplenium angustum Sw., A. auritum Sw., A. cruegeri Hieron., A. delitescens (Maxon) L.D. Gómez, A. juglandifolium Lam., A. salicifolium L., A. serratum L. and A. stuebelianum Hieron.). The majority of the species are epiphytes that grow on decaying trunks inside the forest. For this family, the registered species correspond to 35% of the species in the Brazilian Amazon, and 40% of species in Pará State.